Study of Quality of Life, Depression, and Daily Routines in Rural Elders in Birjand City, Iran, in 2013 - Sakineh Mesgar; Zahra Amini Nasab; Mohammad Hossein Nakhaei; Gholamreza Sharifzadeh; Seyed Alireza Javadinia (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: With scientific advances taking place in the medical field and increased life expectancy in modern societies, significant growth in the elderly population of our country has been observed in recent years. Elderly people encounter different risks compared to other age groups. In this study, quality of life, depression, and daily routines of rural elders living in Birjand City, Iran were evaluated in 2013. Methods & Materials: This cross-sectional descriptive and analytical study was conducted on 360 rural elders living in Birjand, Iran. Data collection tools were the World Health Organization quality of life 26-item questionnaire, 15-item geriatric depression scale (GDS), 6-item activities of daily living questionnaire (ADL), and 7-item instrumental activities of daily living questionnaire (IADL). Data were analyzed using SPSS ver. 19 and values of P≤0.05 was considered significant. Results: The mean and standard deviation quality of life scores was 77.9±10.4. The mean and standard deviation of depression scores was 5.5±2.9. The mean and standard deviation of ADL was 6.5±1.5, and the mean and standard deviation IADL was 12±3. Significant differences were observed between demographic physical activities, education, marital status, depression, ADL, IADL, and quality of life (P≤0.05). A significant strong inverse relationship (r=-0.56) between QOL and depression and a significant inverse relationship between ADL (r=-0.32) and IADL (r=-0.39) and QOL was observed. Conclusion: The results of this study showed that activities of daily living increases quality of life and reduces depression. According to these results, the health care system authorities should not only plan to increase awareness of the benefits of activities of daily living in old ages, but also provide appropriate environment and programs for the elderly activities in our country.